A new species of Grossera (Euphorbiaceae) from Equatorial Guinea - Barberá, Patricia; Riina, Ricarda; Velayos, Mauricio (Phytotaxa, 2015)
Grossera angustifolia, a new species of Euphorbiaceae from Equatorial Guinea, is described and illustrated. The new species belongs to sect. Grossera and it is most similar to G. paniculata, but the two species can be readily distinguished by several leaf characters. A key for the species of sect. Grossera is provided.